Discussions on playful pedagogical practices: contextualization about Reading projects in the Municipal Network of Santa Maria/RS (Research, Society and Development, 2020)
In this article, a part of the  master’s research, still under development, of the first author, whose theme includes  reading and playfulness in the school context, is presented. Accordingly, the objective is to investigate which playful pedagogical practices are developed  from the reading projects of the Muncipal Teaching Network of Santa Maria/RS, with a view to a discussion on the reading practices in the respective projects. The methodological procedures, through qualitative research, of bibliographic-documental type, have, as theoretical support, the studies of Bardin (2004) whose references supported the data analysis, however the research also includes other authors, such as Brougère (1998), Kishimoto (2003), Luckesi (2014), Santin (1994), Santos (2001), Vygotsky (1987) and Zabala (1998). Among the results, the playful practices stand out from the reading projects are developed through actions that, in different spaces, with students, teachers, school management and external public, extended beyond school geography, involving the participation of the local community, with a view to better reading training for students from the Municipal Network of Santa Maria/RS.